2012
DOI: 10.1002/elan.201100566
|View full text |Cite|
|
Sign up to set email alerts
|

Voltammetric Detection of a Specific DNA Sequence of Avian Influenza Virus H5N1 Using HS‐ssDNA Probe Deposited onto Gold Electrode

Abstract: The working principle of a genosensor is based on the mechanism of ion‐channel mimetic sensors. The analytical signals generated upon hybridization processes were recorded by a redox active marker [Fe(CN)6]3−/4− present in the sample solution using voltammetric techniques. The developed genosensor was suitable for determination of 20‐mer complementary oligonucleotide sequence, and also of the PCR products containing the complementary 20‐mer sequence in various positions, with detection limits in the 10 pM rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…This system was selective. The decrease of reduction/oxidation peak current of 15.1 ± 2.86 % recorded in presence of the fully complementary c-NC3 and 0.67 ± 1.65 % in presence of the non-complementary nc-NC3 target were observed [26]. These data indicated that measuring system based on SPGEs in the comparison to GDEs is more sensitive.…”
Section: Dna Target Derived From Aiv H5n1mentioning
confidence: 74%
See 3 more Smart Citations
“…This system was selective. The decrease of reduction/oxidation peak current of 15.1 ± 2.86 % recorded in presence of the fully complementary c-NC3 and 0.67 ± 1.65 % in presence of the non-complementary nc-NC3 target were observed [26]. These data indicated that measuring system based on SPGEs in the comparison to GDEs is more sensitive.…”
Section: Dna Target Derived From Aiv H5n1mentioning
confidence: 74%
“…The selectivity of the genosensor confirms the lack of response in the case of nc-NC3 sequence. The detection of 20-mer DNA target derived from AIV H5N1 (c-NC3) with using classic gold electrodes modified with SH-NC3/MCH has been already reported [26]. This system was selective.…”
Section: Dna Target Derived From Aiv H5n1mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, in our laboratory, we have developed two genosensors working according to this mechanism based on the modiied gold electrode intended for the detection of speciic DN" sequence of avian inluenza virus "IV H5N1 using NH 2 -ssDN" or HS-ssDN" probes for the modiication of gold electrode [11,12].…”
Section: Methods Of Hybridization Process Detection: Selected Examentioning
confidence: 99%